(untitled) (Raparin Journal of Humanities (RJH), 2026)
In the second half of the last century, organizational activity and arrangement were considered as a part of the political and secret struggle for the parties in South Kurdistan. The organization of the Toilers of Kurdistan, as a political party at this stage, was one of the backbones of the organization’s survival, which, together with the armed movement, played an important role after the armed revolution at the beginning of the 20th century’s last quarter. Pishdar, as a geographical center and a part of its social composition that had high national feelings, helped the development and success of the Kurdistan liberation movement, in which its base and presidency were in the border areas. The community’s assistance, in terms of economic or spiritual, had a good effect on the success of the entire process of organized and army activity that formed the core of the revolution of that period. Pishdar organizations, due to Pishdar’s geographical location, played an active role in political movements and protests, especially in the uprising of Qaladze on April 24, 1982. They also helped the Peshmerga forces in collecting food, medicine, and conveying messages of the other areas to the center, especially after the Anfal period and the slowdown of organized activity in the cities because of the pressure from the regime’s oppressive institutions, they then become the link between the leadership and center of Komala and the isolated cities. What is the role of Kurdistan Laborers Association in Pishdar region in helping and strengthening Kurdistan libration movement? What were the actions of the organization during (1975 - 1989)? In this research, we depend on descriptive and analytical methods for the sake of documentation of the events, oral history has been used.